Topographical Location of H—Y Antigen on Mouse Spermatozoa by Immunoelectronmicroscopy - Koo, Gloria C. (1973)
H-Y (male) antigen was visually located on mouse sperm by electron microscopy, by use of the indirect hybrid antibody method and tobacco mosaic virus as the visual marker. Labeling was achieved by centrifugation of the sperm through a discontinuous gradient consisting of alternating layers of immune reagents and wash solutions. Treated sperm were examined topographically by preparation of platinum-carbon replicas. Antigen was located mainly on the acrosomal cap of the sperm head.